MOM : the digital library system in IIUM Library - Abdullah, Sarifah; Abdullah, Fadzilah (2009)
The IIUM Digital Library is using a content management system (CMS) called Multimedia Object Manager (MOM). It is developed by a Malaysian company namely Paradigm Systems Sdn. Bhd. MOM acts as a repository for all types of IIUM digital materials such as theses, examination papers, IIUM publications, contents page for journals subscribed by IIUM Library, manuscripts and etc.. The system is running on IBM XSeries 365 with 2GB RAM, 80GB hard disk , 2X Intel Xeon 2.4 Processor and SQL Server database. The system consists of two fundamental modules which are content management system and taxonomy browser. It supports Unicode to enable the Library to publish Arabic information resources, and provide full-text access. The system allow to create many content templates, multi-tiered architecture to enables organizations to use information and network more efficiently, scalable performance, conforms to multi-protocol and metadata standards practiced by knowledge professionals such as Dublin Core and XML, robust master repository for management and retrieval of all types of enterprise content and digital assets. This paper will briefly explain on the technical and features of the system as well as shares the Library’s experience in implementing a digital library system by using Multimedia Object Manager (MOM).